Exploring patient safety culture in emergency departments: A Tunisian perspective. (January 2021) - Aouicha, Wiem; Tlili, Mohamed Ayoub; Sahli, Jihene; Dhiab, Mohamed Ben; Chelbi, Souad; Mtiraoui, Ali; Latiri, Houyem Said; Ajmi, Thouraya; Zedini, Chekib; Ben Rejeb, Mohamed; Mallouli, Manel
Highlights: Participants emphasized the lack of patient safety culture in their EDs. Professionals in private EDs had higher scores of patient safety culture. The under-reporting of adverse events reflects fear of retaliation. Patient safety training should focus on promoting patient safety culture. Abstract: Background: Emergency departments (EDs) are considered a high-risk environment because of the high frequency of adverse events that occur within. Measuring patient safety culture is an important step that assists healthcare facilities in planning actions to improve the quality of care provided to patients. This study aims to assess patient safety culture within EDs and to determine its associated factors. Methods: A cross-sectional study conducted among professionals from all the EDs of public and private healthcare institutions in Tunisia. It spread from June to September 2017. We used the validated French version of the Hospital Survey on Patient Safety Culture questionnaire. Results: In total, 11 EDs were included in the study, with 442 participants and a participation rate of 80.35%. All the ten dimensions of patient safety culture were in need of improvement. 'Teamwork within units' scored the highest with 46%, however, the lowest score was attributed to 'the frequency of adverse events reporting' (19.6%). Several factors have been found significantly related to safety culture. Private EDs have shown significantly higher scores regarding nine patient safety culture dimensions. Conclusion: This study showed a concerning perception held by participants about the lack of a patient safety culture in their EDs. Also, it provided baseline results giving a clearer vision of the aspects of safety that need improvement.